Evolution of the Cp-Actin-based Motility System of Chloroplasts in Green Plants - Suetsugu, Noriyuki; Wada, Masamitsu (Frontiers in Plant Science, 2016)
During the course of green plant evolution, numerous light responses have arisen that optimize their growth under fluctuating light conditions. The blue light receptor phototropin mediates several photomovement responses at the tissue, cellular and organelle levels. Chloroplast photorelocation movement is one such photomovement response, and is found not only in most green plants, but also in some red algae and photosynthetic stramenopiles. In general, chloroplasts move toward weak light to maximally capture photosynthetically active radiation (the chloroplast accumulation response), and they move away from strong light to avoid photodamage (the avoidance response). In land plants, chloroplast movement is dependent on specialized actin filaments, chloroplast-actin filaments (cp-actin filaments). Through molecular genetic analysis using Arabidopsis thaliana, many molecular factors that regulate chloroplast photorelocation were identified. In this Perspective, we discuss the evolutionary history of the molecular mechanism for chloroplast photorelocation movement in green plants in view of cp-actin filaments.